(untitled) (Northern International Medical College Journal, 2015)
Digital myxoid cyst is a benign skin disease usually present as solitary or a few soft, translucent to slightly bluish nodule. Here, we report a case of 20 years old lady presented with a slowly growing asymptomatic cystic lesion on her right ring finger for about 9 months considering the rarity of myxoid cyst. Northern International Medical College Journal Vol.5(1) 2013: 318-319